2019
DOI: 10.1371/journal.pone.0224402
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Randot Preschool stereotest: Testability, norms, reliability, specificity and sensitivity in children aged 2-11 years

Abstract: PurposeTo comprehensively assess the Randot Preschool stereo test in young children, including testability, normative values, test/retest reliability and sensitivity and specificity for detecting binocular vision disorders.MethodsWe tested 1005 children aged 2–11 years with the Randot Preschool stereo test, plus a cover/uncover test to detect heterotropia. Monocular visual acuity was assessed in both eyes using Keeler Crowded LogMAR visual acuity test for children aged 4 and over.ResultsTestability was very hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…This is because most subjects with a normal stereo threshold are able to achieve the best threshold value of 20 arcsec on Randot Circles; therefore, there is little discrimination among individuals with different stereo performance. Thresholds on ASTEROID are distributed roughly log normally, in agreement with lab studies of stereoacuity 20 , 26 ; consistent with this, the interquartile range was approximately 1.35× the standard deviation ( Table ), as expected for a normal distribution. In contrast, the interquartile range for the Randot tests is less than their standard deviation, reflecting the highly non-normal distribution of results.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is because most subjects with a normal stereo threshold are able to achieve the best threshold value of 20 arcsec on Randot Circles; therefore, there is little discrimination among individuals with different stereo performance. Thresholds on ASTEROID are distributed roughly log normally, in agreement with lab studies of stereoacuity 20 , 26 ; consistent with this, the interquartile range was approximately 1.35× the standard deviation ( Table ), as expected for a normal distribution. In contrast, the interquartile range for the Randot tests is less than their standard deviation, reflecting the highly non-normal distribution of results.…”
Section: Discussionsupporting
confidence: 82%
“…We performed statistics on log thresholds, rather than threshold values, as log thresholds are closer to normally distributed (see Ref. 26 for further details). Similarly when combining different thresholds obtained for the same subject, we took the mean of log thresholds (equivalent to the geometric mean of the thresholds).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, they also concluded that the ability of this test to quantify such values in children aged under five years of age is relatively poor. 3 The Randot test is based on discriminating patterns in random dots, and it is one of the most widely used tests in clinical practice. However, Afsari et al reported that the Randot Preschool stereoacuity test was the most reliable and replicable of all of the tests that were compared in their study.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that it is possible for stereoacuity exploration tests such as the Randot test to be used to determine the stereoscopic vision values, observing that subjects aged between three and five years of age attained similar values to those recorded in the adult population. 3 , 4 , 5…”
Section: Introductionmentioning
confidence: 99%
“…b: Bland‐Altman plots showing difference in log arcsec (log 10 θ 2 − log 10 θ 1 ) plotted against the mean (log 10 θ 2 + log 10 θ 1 )/2. A log transform is used since log thresholds are closer to normally distributed than the original log thresholds 44 . Horizontal black line shows 0 difference; solid purple line shows mean of observed differences, or bias; dashed purple lines show the limits of agreement, ±1.96 standard deviations of the observed differences, or 95% coefficient of repeatability; both are given in the text box.…”
Section: Methodsmentioning
confidence: 99%